2001
DOI: 10.2307/3454998
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Extent of the Health Hazard Posed by High-Production Volume Chemicals

Abstract: the goal of providing a humane, economical, and efficient method of collecting basic toxicologic data for HPV chemicals (2-4). For this purpose, HPV chemicals are defined as those produced or imported into the United States in quantities greater than 1 million pounds per year. The program asks chemical producers and importers to voluntarily provide basic toxicologic data on HPV chemicals (5). These chemicals were identified under the Toxic Substance Control Act 1990 Inventory Update Rule (6). Overall, the HPV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…At odds with DEREK and OncoLogic, this approach does not use a priori knowledge on the mechanisms of action or on SAs, but re-analyzes the database of chemicals in order to develop its own rules (i.e., SAs) liking the toxicity of chemicals to their structures. This approach has been implemented into a commercial computer program [29][30][31][32][33][34][35][36][37]. CASE and MULTICASE are a very characterized SAR approach, which is distinguished from other approaches by its central reliance on computer-generated substructural fragments, which are its major type of molecular descriptors, and the completely automated and unbiased manner in which these descriptors are generated and chosen for inclusion in SAR model.…”
Section: Developments Of Sas Knowledge Through Artificial Intelligencmentioning
confidence: 99%
“…At odds with DEREK and OncoLogic, this approach does not use a priori knowledge on the mechanisms of action or on SAs, but re-analyzes the database of chemicals in order to develop its own rules (i.e., SAs) liking the toxicity of chemicals to their structures. This approach has been implemented into a commercial computer program [29][30][31][32][33][34][35][36][37]. CASE and MULTICASE are a very characterized SAR approach, which is distinguished from other approaches by its central reliance on computer-generated substructural fragments, which are its major type of molecular descriptors, and the completely automated and unbiased manner in which these descriptors are generated and chosen for inclusion in SAR model.…”
Section: Developments Of Sas Knowledge Through Artificial Intelligencmentioning
confidence: 99%
“…Following these pioneer works, several mutagenicity programs were developed. White et al challenged the most commonly used programs (CASE/MULTICASE, , DEREK, , TOPKAT , ) with a test set of over 500 proprietary pharmaceuticals and reported a concordance (accuracy) between 72% and 81%. Two recent reviews , examining numerous (Q)SAR models for noncongeneric chemicals reported similar results and stressed the lack of sensitivity (the measure of the ability to correctly identify true positives) as the main limitation of these systems.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major assumptions underlying the HPV programme is that chemicals produced in large volumes pose a greater hazard, on average, than other substances. However, Cunningham & Rosenkranz (5) have documented, by using computerised structure-activity relationship analysis, that "for all toxic effects (including mutagenicity, genotoxicity, carcinogenicity, and developmental toxicity) except one (the in vitro induction of [sister chromatid exchanges]), the proportion of chemicals predicted to be toxic among the HPV sample was significantly less than the proportion of chemicals predicted to be toxic in the [non-HPV] reference set". Likewise, the popular assumption that substantial "knowledge gaps" exist (1) does not withstand even a cursory review of the published literature for HPV chemicals (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%